Tobacco smoking and the risk of sudden cardiac death: a systematic review and meta-analysis of prospective studies - Aune, Dagfinn (Eur J Epidemiol, 2018)
Smoking is an established risk factor for cardiovascular disease including coronary heart disease and stroke, however, data regarding smoking and sudden cardiac death have not been summarized in a meta-analysis previously. We therefore conducted a systematic review and meta-analysis to clarify this association. We searched the PubMed and Embase databases for studies of smoking and sudden cardiac death up to July 20th 2017. Prospective studies were included if they reported adjusted relative risk (RR) estimates and 95% confidence intervals (CIs) for smoking and sudden cardiac death. Summary RRs were estimated by use of a random effects model. Twelve prospective studies were included. The summary RR was 3.06 (95% CI 2.46–3.82, I(2) = 41%, p(heterogeneity) = 0.12, n = 7) for current smokers and 1.38 (95% CI 1.20–1.60, I(2) = 0%, p(heterogeneity) = 0.55, n = 7) for former smokers compared to never smokers. For four studies using non-current (never + former) smokers as the reference category the summary RR among current smokers was 2.08 (95% CI 1.70–2.53, I(2) = 18%, p(heterogeneity) = 0.30). The results persisted in most of the subgroup analyses. There was no evidence of publication bias. These results confirm that smoking increases the risk of sudden cardiac death. Any further studies should investigate in more detail the effects of duration of smoking, number of cigarettes per day, pack-years, and time since quitting smoking and sudden cardiac death. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10654-017-0351-y) contains supplementary material, which is available to authorized users.